Rancangan Sistem Pendataan Siswa Berprestasi Berbasis Mobile Dengan Metode Waterfall - Alda, Muhamad; Sabrina Putri; Adhe Eva Yolanda; Syaidah Fiddarain (Bulletin of Computer Science Research, 2024)
This research aims to facilitate the process of collecting data on high achieving students so that the data obtained is more accurate. To overcome the problems faced, the author will provide alternative problem solving by developing a system based on currently running computerized mobile-based data that uses codes and databases. A system that will be built using the waterfall method. This method was chosen because it describes a systematic and sequential approach. The conclusion of this research is that a mobile-based student achievement data collection application can provide a solution for managing student achievement data with accuracy. The system used using codular can be used easily. The design and code blocks used can be understood easily unlike other tools that require programmers to memorize the programming language that will be used later. Here, by using the application maker code has been provided blocks that will be arranged and make it a system that will run as we wish. With today's developments, making mobile applications is something we must learn in such a way as not to be left behind with today's technological developments. Because, with this mobile-based application, the application used can be used flexibly.